The Influence of Attendance Levels in Weekly Group Meetings at Bekasi Branch of Permodalan Nasional Madani (PNM) - Petrus Agus Mulyono (Formosa Journal of Sustainable Research, 2023)
In alleviating poverty in Indonesia and one of the problems of MSME is access to capital to expand their business, the Government of Indonesia established an institution or non-bank financial institution called Permodalan Nasional Madani. PT. PNM makes a business product called Mekaar (Fostering a Prosperous Family Economy) with the aim of improving the welfare of Indonesian families where this Mekaar product focuses on underprivileged women entrepreneurs. This study aims to describe the frequency of attendance of group members in weekly meeting activities and their impact on Mekaar's business. This study uses a qualitative descriptive approach with interviews and documentation studies, analysis using an interactive analysis model which includes data collection, data reduction, data presentation and drawing conclusions as well as data validity techniques carried out by means of triangulation techniques. Respondents used included Mekaar Managers, Mekaar Area’s Head, Mekaar Unit’s Head, Group Leaders, Customers, and AO PNM Mekaar Bekasi City. It is expected that the results of this study can determine the effect of attendance rates and what factors affect the attendance rate of group members in weekly meetings